IMPLEMENTASI KEBIJAKAN PEMBERIAN BERAS SEJAHTERA (RASTRA) DI KELURAHAN BLAMBANGAN KECAMATAN BLAMBANGAN UMPU KABUPATEN WAY KANAN. - Rola Pola Anto; Yessie Anggiarista (e-JKPP, 2019)
The problem in this research is that, (1) How is the implementation policy of rice for prosperous in the village Blambangan District Blambangan Umpu Way Kanan? (2) What aspects inhibit the implementation of the rice-feeding policy  in the village Blambangan Blambangan District Umpu Way Kanan?This study uses a qualitative research type with a descriptive analysis method. The use of this method is to describe the policy of giving Rice Sejahtera (Rastra), in the village Blambangan District Blambangan Umpu Way Kanan, reviewing qualitative, how all data is obtained directly from the informant With interviews and obsevation.Based on the results of the research, that the rice feeding policy, through the dimension (1) The ideal policy, that the Government's policy to provide a very helpful community in fulfilling basic life needs, (2) The objectives Policy, has been in accordance with government policy to help the poor family, but can not be implemented optimally because there are still poor families who can not pay the rice for its area, (3). Implementing organization has been made according to the needs, but in the implementation is not in accordance with the functions and authority of each field, even impressed the organization is less running, its implementation because the employees are appointed relative Little, so Lurah still dominates the Rice division system, (4) environmental factors, has been in accordance with the presence of rice for prosperous in the village, but can not reduce the poverty rate.  The inhibiting aspects are: (1) not effective in the implementation of the policy, (2) the relative lack of resource capabilities in the implementation of the Policy rice for prosperousin the village, (3) Inadequate work facilities, the warehouse of rice shelters, and even partly The existing rice was placed at the house of Lurah, so it could interfere in its management.